Small intestinal mucosal toxicity of cis-platinum--comparison of toxicity with platinum analogues and dexamethasone. - Allan, S. G. (Nature Publishing Group, 1986)
Cis-platinum causes profound gastrointestinal symptoms in patients and these may persist for many days after drug administration. Gut mucosal toxicity may be a factor in the pathogenesis of such prolonged nausea, vomiting and anorexia. The effects of cis-platinum on mouse ileal mucosal architecture, villus epithelial cell influx and disaccharidase activity are described in comparison with dhe effects of two platinum analogues, CBDCA and CHIP. In addition the effect of dexamethasone, a useful drug in the palliation of cis-platinum-induced emesis, in combination with cis-platinum is described. Cis-platinum, CBDCA and CHIP cause profound reduction in crypt cell production rate (CCPR) and thus villus epithelial cell influx within hours of administration leading to villus stunting and diminished function. CBDCA showed the least profound effect with early rebound in CCPR by day 3. Cis-platinum and CHIP were roughly equitoxic to ileal crypts with rebound in CCPR being delayed until day 7. Similarly, CBDCA caused least reduction in disaccharidase activity with cis-platinum and CHIP being equitoxic. The addition of dexamethasone had no protective effect on the effects of cis-platinum on murine ileal mucosa and mice given the combination chronically had no weight gain over 18 weeks, their weight paralleling those receiving cis-platinum alone. The platinate compounds have differing degrees of intestinal mucosal toxicity but no direct inference can be drawn in respect to the clinical situation where CBDCA causes less gastrointestinal symptomatology than CHIP but where both cause less than cis-platinum. Dexamethasone does not act by mucosal protection to provide its useful effects in prolonged cis-platinum-induced gastrointestinal symptoms.